Benny the blue whale a descent into story, language and the madness of ChatGPT - Stanton, Andy 1973- (Oneworld Publications, 2023)
When a friend introduces him to ChatGPT, the new large language chatbot, Andy is as sceptical as he is curious. Can this jumble of algorithms really mimic the spontaneity of human thought? Could it one day replace human authors like him for good? And are we soon to be ruled over by despotic robot overlords
Keywords: Künstliche Intelligenz; Automatische Sprachproduktion; Kreatives Schreiben; ChatGPT; Literaturproduktion; Autorschaft; ChatGPT.; Technology / Social aspects; Creative writing / Technological innovations; Authorship / Technological innovations; Natural language generation (Computer science); Création littéraire / Innovations; Art d'écrire / Innovations; Génération automatique de texte